Digital Schism: The Reconstruction of Religious Authority and the Emergence of Islamic Knowledge Elite in the AI Era - Rois, Choirur; Yazdani, Gholamreza (MD Research Center, 2026)
This study aims to analyze the reconstruction of Islamic religious authority and the emergence of an Islamic knowledge elite in the digital era mediated by artificial intelligence (AI). The study’s background stems from the phenomenon of digital transformation, which is shifting religious authority from centralized formal institutions such as Islamic boarding schools (pesantren) to decentralized virtual spaces through algorithmic platforms and chatbots like “AI Mufti”. The research employs an exploratory literature review method with a qualitative approach, collecting and analyzing indexed scholarly articles and recent publications related to concepts of digital authority, algorithms, and the Islamic knowledge elite. The findings identify the occurrence of a “digital schism”, an epistemic tension between the hierarchical logic of sanad (chains of transmission) and the distributed logic of algorithms, which gives rise to a new knowledge elite, such as dakwah influencers and AI muftis, whose legitimacy is constructed through digital performativity and symbolic capital. The conclusion and core argument of this research is that the transformation of Islamic religious authority in the digital age is not merely a shift in medium, but a fundamental epistemological reconstruction, necessitating a new paradigm to integrate Islamic values with modern technological rationality.